(untitled) (International Journal of Islamic Business, 2017)
Global Financial Crisis (GFC) in 2007-2010 has given a big impact to the financial institution and banking institutions worldwide. A wide array of GFC impact is experienced by the operating and financial performance in banking institutions. Islamic banks however have raised the public interest to be relatively unaffected by the GFC. There are studies which found that GFC has less effect to Islamic banking system. In fact it is claimed to be â€œimmune from the ravages of the GFCâ€. The question arises whether the claim is also true in the case of the Islamic bank financing. Thus, this study attempts to assess the reaction of Islamic bank financing to the Global Financial Crisis (GFC) through the monetary policy action taken by the government in Malaysia. Using the time series data the investigation will benefit from the quarterly data spanning from 1995 to 2013. A model is constructed and focusing on the interaction term of monetary policy and global financial crisis. In analyzing the impact and a long run relationship between variables, Johansenâ€™s co-integration test is applied. Finding shows that Islamic bank financing and the interaction term of global financial crisis are co-integrated and, hence, a long-run equilibrium relationship exists between them. This finding also implies despite the prior claims that Islamic bank financing is unharmed with the Global Financial Crisis (GFC), the reaction of Islamic bank financing in Malaysia is sensitive towards the global financial crisis but through monetary policy action taken by the government.